Pengaruh Pajak dan Dana Transfer Pusat Terhadap Belanja Modal Di Indonesia Timur: Pengaruh Pajak dan Dana Transfer Pusat Terhadap Belanja Modal Di Indonesia Timur - Asiyah Asiyah; Lucky Rachmawati (Universitas Negeri Surabaya, 2026)
Eastern Indonesia has high development potential, yet local governments face fiscal constraints, particularly because local tax revenue is relatively low, making capital expenditure heavily reliant on fiscal transfers. This study examines the effect of Local Taxes, Fiscal Transfers (DAU, DBH, DAK), and Regional Incentive Fund (DID) on Capital Expenditure in 12 provinces during 2018–2024. Panel data were analyzed using STATA 14 with a Random Effect Model (REM). Results show that, individually, Local Taxes and DAU negatively and significantly affect Capital Expenditure, while DBH and DAK have positive and significant impacts. DID has no significant effect. Simultaneously, all variables significantly influence Capital Expenditure, indicating that the combination of local revenue and fiscal transfers determines capital spending capacity. The findings highlight that fiscal transfers are the primary driver of capital expenditure, offering key insights for regional fiscal policies to enhance effectiveness and financial autonomy of capital spending.